Li Lun, lad of courage - Treffinger, Carolyn; Wiese, Kurt, 1887-1974 (New York : Walker, 1995)
Because of his fear of the sea, a young Chinese boy is sent to a distant mountain where he proves his bravery.
Originally published: Nashville : Abingdon-Cokesbury Press, 1947.
Keywords: Courage -- Fiction; China -- Fiction